2012
DOI: 10.1038/mp.2012.169
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced functional link between valuation networks in abstinent heroin-dependent subjects

Abstract: Using neuroeconomic approaches, our findings demonstrate that the underlying duality of the β-δ discounting networks that jointly influence valuation is impaired to a pathogenic state in abstinent heroin dependents. The imbalanced functional link between the β-δ networks for valuation may orchestrate the irrational choice in drug addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 11 publications
2
37
0
Order By: Relevance
“…That processing in the nucleus accumbens core can indeed influence DA transmission in the aDLS was further demonstrated using in vivo voltammetry in rats self-administering cocaine in which late-developing, drug CS-evoked DA transients in the aDLS were completely prevented by a specific nucleus accumbens core (NAcbC) lesion (Willuhn et al 2012). Remarkably, functional coupling between the ventral and the dorsal striatum has also been shown in former heroin addicts, together with decreased functional coupling between the striatum and the PFC (Xie et al 2014). Neurocomputational models of addiction have successfully incorporated this concept (Dezfouli et al 2009, Piray et al 2010, which may be linked to earlier notions of a reinforcement learning model, which assigns the role of critic to the nucleus accumbens that modulates the actor role over action selection assigned to the dorsal striatum (O'Doherty et al 2004).…”
Section: Transition From Ventral To Dorsal Striatummentioning
confidence: 88%
“…That processing in the nucleus accumbens core can indeed influence DA transmission in the aDLS was further demonstrated using in vivo voltammetry in rats self-administering cocaine in which late-developing, drug CS-evoked DA transients in the aDLS were completely prevented by a specific nucleus accumbens core (NAcbC) lesion (Willuhn et al 2012). Remarkably, functional coupling between the ventral and the dorsal striatum has also been shown in former heroin addicts, together with decreased functional coupling between the striatum and the PFC (Xie et al 2014). Neurocomputational models of addiction have successfully incorporated this concept (Dezfouli et al 2009, Piray et al 2010, which may be linked to earlier notions of a reinforcement learning model, which assigns the role of critic to the nucleus accumbens that modulates the actor role over action selection assigned to the dorsal striatum (O'Doherty et al 2004).…”
Section: Transition From Ventral To Dorsal Striatummentioning
confidence: 88%
“…As a result, the weaker δ-network FC strength, coupled with stronger β-network FC strength, implicated the mutually reinforcing pattern to synergistically tilt the network balance toward motivational drive and lead to impulsive behaviors (i.e., δ i - β i value is negative). It has been suggested that this imbalanced neural mechanism may be the neural underpinning of aberrant behaviors in drug addiction (Volkow et al, 2013; Xie et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…At the neurobiological level, addicted rats are characterized by an impairment in synaptic plasticity in the ventral striatum [93] and its cortical afferent, the medial prefrontal cortex [66], suggesting that addiction, at least to cocaine, is associated with impaired fronto-striatal connectivity in rats, as it has been shown in alcoholics [96] or former heroin addicts [97]. These findings are also in agreement with a recent demonstration that altered synaptic plasticity in the prelimbic cortex supports compulsive drug-seeking behavior in rats trained in a seeking-taking task [26] (see below).…”
Section: Instrumental and Pavlovian Mechanisms Subserving Drug Use: Dmentioning
confidence: 99%